Pengaruh Kepemimpinan Dan Kompensasi Terhadap Kinerja Karyawan Di Yayasan Tinta Emas Indonesia - Rini Permata Sari; Hasanuddin Hasanuddin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the influence of leadership and compensation on employee performance at the Yayasan Tinta Emas Indonesia. This type of research is quantitative. The sampling technique used is saturated sampling where the number of population and samples is 52 respondents. Data collection using a questionnaire that has been tested for validity and reliability. Data processing using SPSS Version 26. Data analysis techniques are carried out using multiple linear regression analysis. And the results of this study indicate that: (1) The leadership has a positive and significant effect on employee performance. (2) The compensation compensation has a positive and significant effect on employee performance. (3) The leadership and compensation have a positive and significant effect on employee performance. This research provides advice for the foundation to provide direction to its subordinates so that employees can be motivated by a good leadership role and consider anything related to compensation, both direct compensation and indirect compensation.